SAP Protein Dependent Natural Killer T-Like Cells Regulate the Development of CD8(+) T Cells with Innate Lymphocyte Characteristics - Verykokakis, Mihalis (2010)
CD8(+) T cells are selected via low affinity interaction with MHC class I molecules on thymic epithelial cells (TECs). However, compromised T cell receptor signaling was proposed to force CD8(+) T cell selection on hematopoietic cells through a SLAM-associated protein (SAP)-dependent mechanism similar to NKT cells. The outcome is an unconventional CD8(+) T cell with phenotypic and functional characteristics of innate lymphocytes. Here we showed that Id3(−/ −) CD8(+) T cells had an innate-like phenotype and required SAP for their development. However, like conventional CD8(+) T cells, Id3(−/ −) CD8(+) thymocytes were selected on TECs. The requirement for SAP and the innate-like phenotype was not intrinsic to Id3(−/ −) CD8(+) thymocytes. Rather, an expanded population of NKT-like cells induced the innate phenotype on CD8(+) T cells through production of interleukin-4. Our findings reveal that accumulation of NKT-like cells promotes conventional CD8(+) thymocytes to acquire innate lymphocyte characteristics.